FPGA Implementation of Sensorless Field Oriented Current Control of Induction Machine - Shah, Vaibhav; Prakash N., Krishna (IEEE International Conference on Computational Intelligence and Computing Research, 2017)
In this paper, Field programmable gate array (FPGA) based prototyping of sensorless Field Oriented Current Control of an induction machine (IM) is discussed. The Field Oriented Current Control is simulated in MATLAB/Simulink using HDL Coder. The synthesizable VHDL code generated was implemented in Xilinx Spartan-3 FPGA and has been tested experimentally to drive a 1.5 kVA squirrel cage IM. Simulation and implementation results are compared and presented here. The results show an improvement in IM drives control by using FPGA in place of a digital signal processor and digital signal controller.